Anxiety as a Stress-Coping Strategy in Positive Psychotherapy: Case Report - Anna Savinova (The Global Psychotherapist, 2025)
This case study demonstrates how Positive psychotherapy addressed chronic anxiety in a 22-year-old female client with prolonged stress exposure. The client presented with rigid perfectionism, autonomic symptoms, and social withdrawal rooted in childhood trauma. Using the Balance Model, therapy targeted: (1) restructuring dysfunctional basic concepts (diligence vs. hope conflict), (2) rebuilding trust through the five-stage process (extended verbalization phase for trauma processing), and (3) reactivating primary capacities (patience, contact). Key interventions included transcultural parables for cognitive flexibility and "small steps" experiments in the achievement dimension. After 42 sessions, the client achieved reduced anxiety, resumed social activities, and developed self-compassion statements. The case highlights PPT’s efficacy in transforming anxiety from a pathological symptom into a growth signal. Findings suggest that modified stage sequencing benefits trauma clients with perfectionism.